Sexually transmitted infections - Barlow, David, M.R.C.P (Facts (Oxford, England), 2011)
With all the attention heaped upon the most deadly sexually transmitted infection of all, HIV, other non-fatal forms of infection have been somewhat neglected, and even overlooked in sexual education. However, incidences of STIs such as chlamydia and gonorrhoea have been dramatically and silently rising in many parts of the world in recent years - though receiving far less attention. It is now recognized that this is a major public health issue, affecting thousands of people, irrespective of background, education or social class. In Sexually Transmitted Infections: The Facts, David Barlow, for t.